Relevance and impact of Biology and Science Education theses in the national context: three decades of research at Universidad Nacional, Costa Rica (Innovaciones Educativas, 2022)
This research aimed to analyze all the undergraduate thesis research of the School of Biological Sciences of Universidad Nacional encompassing a period of 35 years (1985-2019). A total of 418 theses were analyzed and categorized according to bibliometric features, such as year, career, subject, and country area. In addition, theses from the last decade (2009-2019) were consulted in Google Scholar and other electronic databases. Finally, all thesis titles were analyzed by text mining to determine the most frequent concepts by career. It was found that 26.5% were theses in marine and freshwater resource management, 52.7% in natural resource management, and 20.8% in science education. The analysis of theses from the last decade (2009 and 2019) showed that 26% generated publications in indexed journals, of which 69% were in Spanish, and 75% included the student as the first author. The Biology major is dominated by topics applied to resource management and aquaculture. The Teaching Science career plan advocates the design of experiences to enhance and improve teaching and learning processes in various disciplinary and pedagogical fields. These results evidence the coincidence between emerging topics of national interest, specifically in science and biology teaching. In addition, it points out that there is a delay in disseminating the scientific heritage that emerges from the theses and that it is an urgent challenge that these studies transcend beyond the university repositories.
Keywords: bibliometrics; higher education; literature; thesis; research; publication